The motivation of mission statements: How regulatory mode influences workplace discrimination - Kanze, Dana; Conley, Mark A.; Higgins, E. Tory (Organizational behavior and human decision processes, 2021)
•We examine the influence of motivational messaging on workplace discrimination.•The regulatory mode of mission statements predicts discrimination activity.•Discrimination is associated with motivational messaging high in locomotion mode.•This risk can be counteracted with language that is high in assessment mode.•Consideration of ethical standards mediates this effect due to need for expediency.•We introduce a regulatory mode dictionary to help evaluate motivational language. Despite concerted efforts to enforce ethical standards, transgressions continue to plague US corporations. This paper investigates whether the way in which an organization pursues its goals can influence ethical violations, manifested as involvement in discrimination. We test this hypothesis among franchises, which employ a considerable amount of low-income workers adversely affected by discrimination. Drawing upon Regulatory Mode Theory, we perform a linguistic analysis of franchise mission statements to determine their degree of locomotion and assessment language. EEOC archival data for the past decade reveals that regulatory mode predicts franchise involvement in discrimination. Discriminatory behavior is associated with franchises whose mission statements motivate employees to embrace urgent action (locomotion mode) over thoughtful consideration (assessment mode). Two experiments demonstrate that participants exposed to high locomotion mission statements tend to disregard ethical standards due to their need for expediency, making significantly more discriminatory managerial decisions than those exposed to high assessment mission statements.